Cold-tolerant Clostridium spp. related to meat spoilage in cattle farms in Austria - Dorn-In, Samart; Zand, Vanessa; Angerer, Joachim; Ozbek, Kahraman; Eibl, Cassandra; Schwaiger, Karin (Academic Press Ltd- Elsevier Science Ltd, 2025)
Many cold-tolerant Clostridium spp. are responsible for the spoilage of vacuum-packed meat. Cattle can ingest the bacteria via the soil and the environment when grazing or via the feed. Since cattle farming in Austria's Alpine regions is often practiced as pasture-based farming, the aim of this study was to investigate the prevalence of cold-tolerant clostridia in cattle in these regions, to identify the species detected, and to determine the growth temperature of the isolated clostridia. For this purpose, 260 faecal and 260 hide wipe samples were taken from 260 healthy adult cattle from 26 farms in the provinces of Salzburg and Tyrol. The samples were analysed using qPCR, sequencing, and cultural methods. Using qPCR, 22.3 % of the faecal samples were positive for C. estertheticum, 33.8 % for C. tagluense-like, 32.7 % for C. bowmanii, 11.2 % for C. frigoriphilum, and 14.2 % for C. gasigenes. The isolation rates of the species from the PCR-detected samples ranged from 4.7 % to 59.5 %. In addition, nine different Clostridium species were isolated by culture, with C. subterminale, Lacrimispora algidixylanolytica (syn. C. algidixylanolytica), C. tagluense, and C. botulinum being found most frequently. The prevalence of cold-tolerant clostridia in the investigated faeces was relatively high, while in the hide swab samples it was very low. The latter could be related to the lower contamination of the hide with dirt and faeces. The results of this study provide useful information for slaughterhouses, which should pay attention to cleanliness and hygiene during dehiding and evisceration to avoid further contamination of the meat.
Keywords: C. estertheticum; Beef; Cow faeces; Hides; PCR